Novel Circular RNA CircSLC2A13 Regulates Chicken Muscle Development by Sponging MiR-34a-3p - Jiao, Zhenhai; Xie, Tingting; Wang, Xiaotong; Guo, Dongxue; Lin, Shudai; An, Lilong; Lin, Junyuan; Zhang, Li (Journal of agricultural and food chemistry, 2024)
The skeletal muscle is the major muscle tissue in animals, and its production is subject to a complex and strict regulation. The proliferation and differentiation of myoblasts are important factors determining chicken muscle development. Circular RNAs (circRNAs) are endogenous RNAs that are widely present in various tissues of organisms. Recent studies have shown that circRNA plays key roles in the development of skeletal muscles. The solute carrier (SLC) family functions in the transport of metabolites such as amino acids, glucose, nucleotides, and essential nutrients and is widely involved in various basic physiological metabolic processes within the body. In this study, we have cloned a novel chicken circular RNA circSLC2A13 generated from the solute carrier family 2 member 13 gene (SLC2A13). Also, circSLC2A1 was confirmed by sequencing verification, RNase R treatment, and reverse transcription analysis. Currently, our results show that circSLC2A13 promoted the proliferation and differentiation of chicken myoblasts. The double luciferase reporter system revealed that circSLC2A13 regulated the proliferation and differentiation of myoblasts by competitive binding with miR-34a-3p. In addition, results indicated that circSLC2A13 acts as a miR-34a-3p sponge to relieve its inhibitory effect on the target SMAD3 gene. In summary, this study found that chicken circSLC2A13 can bind to miR-34a-3p and weaken its inhibitory effect on the SMAD family member 3 gene (SMAD3), thereby promoting the proliferation and differentiation of myoblasts. This study laid foundations for broiler industry and muscle development research.